Managing forest genetic resources as a strategy to adapt forests to climate change: perceptions of European forest owners and managers - Vinceti, Barbara; Manica, Mattia; Lauridsen, Nina Olsen; Verkerk, Pieter Johannes; Lindner, Marcus; Fady, Bruno (Springer, 2020)
Managing genetic diversity is of key importance in fostering resilience of forest ecosystems to climate change. We carried out a survey reaching over 200 forest owners and managers from 15 European countries to understand their perceptions of the main threats to forest ecosystems, their knowledge of forest genetic resources (FGR) and their attitude toward actively managing these resources to strengthen the resilience of forest ecosystems to climate change. Respondents perceived pests and diseases to be the top-ranking threats to forests, followed by windstorms and drought, with differences across countries. They stated to be aware of the potential offered by managing FGR and indicated that they paid attention to origin and quality in their choice of planting material. Generally, respondents showed a positive attitude in using forest reproductive material foreign to the planting site, to better match the projected future climate conditions, introducing either a new native tree species or a new non-local genotype of a species already planted (keeping the same species but changing the source of planting material). However, forest reproductive material from local sources was largely preferred over non-local material (both genetically improved and not improved). Forest managers and owners may need to be exposed to more evidence of the potential benefits deriving from active adaptation and mitigation management of FGR before implementing adaptive measures. Also, more efforts should be invested in understanding perceptions and motivations of European forest owners and managers, in order to better tailor advice on optimal measures to counteract the detrimental effects of climate change.